Effect of heat treatment on microstructure and properties of hybrid manufacturing TC4 alloy bonding zone - Jun Zhang; Peizhi Yang; Haiou Yang; Wenzhe Yang; Kuitong Yang; Wenya Xu (Journal of Materials Research and Technology)
Samples were deposited on the casting matrix of TC4 titanium alloy by arc fuse additive manufacturing technology. The effects of different heat treatments on the microstructure and properties of the bonding zone of the hybrid manufacturing sample were studied. Meanwhile, the corrosion resistance of different regions of the sample after heat treatment was studied. The results show that with the increase of annealing temperature, the α phase in the binding zone has a certain degree of coarsening, and the acicular martensite α 'phase at the top of the binding zone decomposes. At the same time, the yield strength reached 882.4 MPa when the annealing temperature is 800 °C. After solution aging treatment at 950 °C/1h/AC (Air Cooling)+600 °C/4h/AC, the non-uniformity of the structure of the bonding zone is improved, and the yield strength above 800 MPa is maintained at the highest post-fracture elongation of 8.6%, which demonstrates a good comprehensive performance. On the other hand, after 950 °C/1h/AC+600 °C/4h/AC solution aging treatment, the fusing of the continuous α phase and the decomposition of the acicular martensite α′ phase led to an improvement in the corrosion resistance of the bonding zone. At the same time, the improvement in the microstructure heterogeneity between different regions reduces the difference of corrosion resistance in different regions of TC4 titanium alloy components to a certain extent.